Physical Activity Levels of Junior High School Adolescents During The COVID-19 Pandemic - Ferdianti, Nuraini Melika; Rasni, Hanny; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2023)
The phenomenon of the COVID-19 pandemic has just ended, but one can still remember that the COVID-19 pandemic was a period that had an impact on people's lives. Teenagers are also affected by this pandemic. The social restrictions previously set by the government forced the physical activity of youth to decrease, especially learning activities at school which were stopped and replaced with online learning. This causes a decrease in physical activity in adolescents. The researcher used a descriptive observational method with a cross sectional approach and used cluster random sampling as a sample. The sample used in this research was 675 students. The research used the Physical Activity Questionnaire for Adolescents (PAQ-A) questionnaire. The results of data collection were processed using one-sample Kolmogorov-Smirnov. The results of this study found that the number of female respondents in this study was more than the number of male respondents with a total of 386 female respondents (57.2%). The highest number of respondents was at the age of 15 years with a total of 216 students (32.0%), and the highest student class category was in class IX with a total of 323 students (47.9%). The extracurricular most frequently participated in by respondents in this study was futsal with a total of 102 students (15.1%). The results showed that most of the students' physical activity level was at a low level, with a total of 419 students (62.1%). The conclusion of this research is that the majority of teenagers' physical activity levels are still low.